Religious socialization among Malaysian Muslim adolescents: a family structure comparison - Krauss, Steven Eric; Hamzah, Azimi; Ismail, Ismi Arif; Suandi, Turiman; Hamzah, Siti Rabaah; Dahalan, Dzuhailmi; Idris, Fazilah (Religious Research Association, 2012)
Despite the plethora of research on correlates of adolescent religiosity, few studies have examined the contribution of socialization factors to adolescent religiosity in the context of non-Western Muslim samples from different family contexts. To address this gap, the current study explored the contribution of parenting (direct socialization) and community engagement (indirect socialization) factors on religiosity among 895 Malaysian Muslim high school students from single-/non-parent and two-parent families. T-test results showed that religiosity was higher for students from two-parent families than single-/non-parent parent homes. After controlling for (a) social desirability, (b) gender and (c) school type, the hypothesized factors of: parental attachment, parental religious socialization, parental supervision, youth organization involvement, school attachment, and mosque involvement significantly predicted religiosity for the full sample of students from both types of families. Hierarchical regression results further revealed that while both indirect and direct parental socialization factors were stronger predictors of religiosity for two-parent families than single-/non-parent families, direct parental socialization effects were more robust. Implications of the findings are discussed.